Relationship Between Psychological Well-Being and Quality of Life Among Teachers In Kuala Terengganu - Rameli, Nor Af’Idah; Hassan, Azmi; Mohamad, Abdul Manan (School of Social Sciences, USM, 2017)
The main purpose of this study was to investigate the relationship between psychological wellbeing and quality of life among teachers in Kuala Terengganu. The participants consist of 380 teachers from 36 secondary schools in Kuala Terengganu, Terengganu with the division of 113 male teachers and 267 female teachers. The respondents were randomly selected and the data were gathered through the distribution of questionnaire. The questionnaire used consists of two main scales which are Ryff’s Psychological Well-Being Scale consist of 54 items reflecting the six areas of psychological well-being which are autonomy, environmental mastery, personal growth, positive relation with others, purpose in life, and self-acceptance and World Health Organization Quality Of Life Scale (WHOQOL-BREF) consist of 26 questions covering four domains of factor contributing to quality of life – physical health, psychology, social relation and environment. The finding of the study indicate that the level of psychological well-being among teachers was in the moderate level where majority 350 (92.1%) of the respondents got moderate score and 30 (7.9%) of them got high score of psychological well-being, while the level of quality of life among teachers was in the high level where majority 336 (88.4%) of the respondents got high score and 44 (11.6%) of them got moderate score. Further, Pearson correlation analysis revealed that there was positive relationship ( r = 0.332**, p= 0.00 ) between psychological wellbeing and quality of life among teachers. It shows that the higher level of psychological wellbeing will increase the level of quality of life among teachers. Reflection for future research and occupational health, interventions are suggested.